Prespective and Implementative of The Basis of The Single Prosecution System of The Prosecution of The Prosecution Bill - Priandhika Abadi Noer (Jurnal Independent, 2021)
Revision of Law no. 16 of 2004 concerning the Republic of Indonesia Attorney General's Office is a necessity because of the many changes that have occurred in the field. would replace Law no. 16 of 2004 is the right moment to encourage the Ago to do better. "Change is a necessity. Likewise in legislation, " ini this research concern about the duties and powers of the Prosecutor's Office in the draft law on the prosecutor's office. namely Guidelines on The Role of Prosecutors which serve as guidelines and inspire in the amendment of this Law, especially matters relating to independence in Prosecution, Accountability in Case Handling, Standards of Professionalism, and Protection for Prosecutors. If the Prosecution Bill becomes the new Prosecutor's Law, justice seekers will place the foundation of justice on the prosecutor, so that the prosecution process starting from investigation, investigation, prosecution and execution will optimally realize substantial truth and justice.